Dwustopniowy sposób obliczania pewnego typu płyt ortotropowych - SOKOŁOWSKI, Marek (Engineering Transactions, 1954)
A two stage method of solving orthotropic plate problemsThe problem of numerical calculation of statical quantities (bending moments and shearing forces) for an orthotropic plate subjected to bending is discussed, particular attention being paid to cases where the coefficient ρ (Eq. (2.1)] is less than one.In such cases the coefficients β2 and λ2, appearing in Eqs. (2.4) and (2.5), are complex numbers, which renders the problem a little more complicated.The systems of linear algebraic equations obtained by means of the calculus of finite differences, which correspond to the differential Eqs. (2.4) and (2.5), are solved by using the iteration method, for which two iteration procedures (Arts. 4 and 5) are described for solving problems with complex coefficients.